Determinants of E-commerce Adoption in MSMEs in NTB Mall - Nada Putri Fadilla; Lukman Effendy; Robith Hudaya (Cita Konsultindo Research Center, 2023)
Even though the benefits of e-commerce for MSMEs are enormous, currently not many MSMEs have adopted e-commerce, especially in NTB. Therefore, it is necessary to know what factors actually encourage MSMEs to adopt e-commerce. However, research on e-commerce has only been carried out on large-scale businesses, while studies on small and medium-sized companies, especially regarding the adoption of e-commerce, have not been widely carried out. So, this research is important to do to find out what factors are driving the adoption of e-commerce, especially MSME players who are members of the NTB Mall application. The primary data used in this study came from questionnaires distributed to MSMEs in the NTB Mall application according to the sample characteristics determined by the researcher. The sampling technique used in this research was purposive sampling method. The number of samples in this study was 100 respondents. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS version 3. Based on the results of the study, it can be concluded that environmental factors have a positive and significant influence on e-commerce adoption. Meanwhile, technological factors and organisational factors have a positive but not significant influence on e-commerce adoption.